Osteoarthritis and joint complaints epidemiologic study in town and rural Ural inhabitants - O M Lesnyak; N N Krokhina; O E Alferova; A G Solodovnikov; A G Zakroeva; O F Ryahitsevu; E. M. Avdeeva (Научно-практическая ревматология)
Objective. To study the prevalence of osteoarthritis and joint complaints among urban and rural inhabitants Material and methods. Simultaneous cross-sectional epidemiological study among inhabitants of Revda town and nine rural settlements of Nevijansk farmland in the Sverdlovsk region. Results, questionnaire-based survey showed that the prevalence of joint pain and complaints of joint swelling was higher in the rural population (44,9% and 16,7% correspondingly) compared to town population (26,4% and 6,7% correspondingly), p<0,05. Prevalence of OA in town (11,4%) and in rural population (11,2%) was similar. Higher prevalence of joint complaints in rural population is attributed to higher rate of soft tissue and vertebral involvement, and platypodia. Prevalence of OA in women was almost 3 times higher than in man (town women — 17,8%, town men — 3,7%; rural women — 15,7%; rural men — 5,4%). Age-specific features were also identified. Prevalence of OA in rural population was higher in age group under 50 years (3,18% in town population compared to 7,66% in rural population for age group 41 -50 years), but after 70 years prevalence of OA became significantly (p<0,05) higher in town population (40,34% in town population compared to 20,51% in rural population forage group 71-80 years), and started to decrease in rural population. Conclusion. Joint complaints (pain and swelling) arc common signs in both rural and town population in the Urals, Ihey are more prevalent in older age groups and in rural population. OA prevalence was similar in town and rural population, because joint complains in rural populations were attributed to soft tissue and vertebral involvement, and platypodia.